RECONSTRUCTION OF MAQAM MODES IN THE UZBEK CHANG INSTRUMENT BASED ON MODERN ACOUSTIC APPROACHES - Nizomova Mohinur Ulug‘bek Qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the reconstruction of maqam modes in the Uzbek chang instrument using modern acoustic approaches. The study focuses on analyzing traditional maqom tuning systems, identifying microtonal intervals, an applying acoustic modeling techniques to optimize pitch accuracy and tonal stability. By combining historical performance knowledge with contemporary measurement and simulation methods, the research aims to recreate maqam structures faithfully while enhancing consistency and expressive potential. The findings provide practical guidance for musicians, educators, and instrument makers, contributing to the preservation and modernization of Uzbek musical heritage.